The profitability of banks in a context of negative monetary policy rates: The cases of Sweden and Denmark - Christophe Madaschi; Irene Pablos Nuevo (European Central Bank (ECB), 2017)
This paper looks at how the profitability of banks in Sweden and Denmark has evolved in the context of negative interest rates. Overall, it finds that profitability has continued to improve, even with negative monetary policy rates. Data and model-based evidence confirm that the monetary policy transmission to bank lending rates has so far not been impaired, though they point to a downward stickiness in the bank deposit rate. Swedish and Danish banks rely mainly on wholesale funding to finance their activities, and the fall in wholesale funding costs has led to a significant decline in interest expenses, thereby bolstering the resilience of the net interest income margin. All in all, this has created the prerequisites for positive credit supply developments, and possible unintended consequences of negative monetary policy rates, such as a reduction in credit supply, have not materialised. However, according to Sveriges Riksbank and Danmarks Nationalbank, the prevailing low level of interest rates has aggravated financial stability risks stemming from the large exposure of the banking sector to the housing market in both economies, in a context of rapidly rising housing prices and the resultant growing indebtedness of the household sector.
Keywords: E58; 330; Banks' profitability; monetary policy pass-through